Metallaelectro-Catalyzed C–H Activation by Weak Coordination - Qiu, Youai; Struwe, Julia; Ackermann, Lutz (Synlett, 2019)
The merger of organometallic C–H activation with electrocatalysis has emerged as a powerful strategy for molecular synthesis, avoiding the use of toxic and expensive chemical oxidants in stoichiometric quantities. This review summarizes recent progress in transition-metal-catalyzed electrochemical C–H activation by weak chelation assistance until March 2019.1 Introduction2 Ruthenaelectro-Catalyzed C–H Activation3 Rhodaelectro-Catalyzed C–H Activation4 Iridaelectro-Catalyzed C–H Activation5 Summary and Outlook
Keywords: electrochemistry; C–H activation; metallaelectro-catalysis; transition metals; weak O-coordination